1985
DOI: 10.1039/c39850001414
|View full text |Cite
|
Sign up to set email alerts
|

One- and two-electron pathways in the electrocatalytic reduction of CO2by fac-Re(bpy)(CO)3Cl (bpy = 2,2′-bipyridine)

Abstract: The cyclic voltammetry of fac-Re(bpy)(CO)&I (bpy = 2,2'-bipyridine) and of the intermediate complexes formed by bulk electrolysis in MeCN solution in the presence and absence of C 0 2 has been interpreted in terms of two different electrocatalytic pathways for the reduction of C 0 2 to CO, one involving an initial one-electron reduction and the other an initial two-electron reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
306
2
1

Year Published

1986
1986
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 378 publications
(331 citation statements)
references
References 1 publication
22
306
2
1
Order By: Relevance
“…The air-stable green complex was subsequently isolated and characterized as the rhenium (0) dimer [cfuc-Re (bpy) (CO),}J (10). A recent study carried out in CH,CN with Bu,NPF, as supporting electrolyte agrees with this formulation [64]. Reaction of this complex with HCl gave H, and [Re(bpy) (CO)3Cl] (1; starting complex).…”
supporting
confidence: 74%
“…The air-stable green complex was subsequently isolated and characterized as the rhenium (0) dimer [cfuc-Re (bpy) (CO),}J (10). A recent study carried out in CH,CN with Bu,NPF, as supporting electrolyte agrees with this formulation [64]. Reaction of this complex with HCl gave H, and [Re(bpy) (CO)3Cl] (1; starting complex).…”
supporting
confidence: 74%
“…The high overpotential creates a situation where catalysis can occur without an added proton source. Previous reports have suggested that the oxygen from CO 2 is transferred to an unknown oxide acceptor (19). The oxide acceptor can be a proton that can be extracted from acetonitrile (20) or even from the supporting electrolyte via Hoffman degradation (21).…”
Section: Uv-vis Stopped-flow Spectroscopy: Probing the Selectivity Ofmentioning
confidence: 99%
“…Atmosphere IR spectroscopy 20,53,54 is an ideal tool to monitor the cathodic processes in the studied complexes, due to presence of the carbonyl ligands as strong IR reporters. Table 1 lists the key experimental and calculated vibrational frequencies for the starting complexes and several relevant intermediate and dimer species.…”
Section: Ir and Uv-vis Spectroelectrochemistry Under Inertmentioning
confidence: 99%
“…The anionic pathway is broadly similar to the two-electron pathway observed for Re complexes. 20,21 In contrast, the uncommon second pathway identified using pulsed EPR studies 19 involves coordination of CO 2 to the dimer [Mn(CO) 3 (2,2 -bpy)] 2 in the presence of a Brönsted acid in a concerted oxidative addition step. This process is shown to generate a low-spin Mn II -COOH complex, from which CO is subsequently released.…”
mentioning
confidence: 99%